2010
DOI: 10.1093/molbev/msq219
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale mtDNA Screening Reveals a Surprising Matrilineal Complexity in East Asia and Its Implications to the Peopling of the Region

Abstract: In order to achieve a thorough coverage of the basal lineages in the Chinese matrilineal pool, we have sequenced the mitochondrial DNA (mtDNA) control region and partial coding region segments of 6,093 mtDNAs sampled from 84 populations across China. By comparing with the available complete mtDNA sequences, 194 of those mtDNAs could not be firmly assigned into the available haplogroups. Completely sequencing 51 representatives selected from these unclassified mtDNAs identified a number of novel lineages, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 70 publications
6
79
0
1
Order By: Relevance
“…It is the ancestral haplogroup to almost all European and Oceanian haplogroups in addition to many Asian and Amerindian ones. Superhaplogroup N can be divided into smaller haplogroups such as R, A, I, S, W, X and Y (Kong et al, 2011). Haplogroup N is found in all parts of the world, but has low frequencies in Sub-Saharan Africa, and can be defined by the mutations at position 8701;9540;10398;10873 and 15301 (van Oven and Kayser, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is the ancestral haplogroup to almost all European and Oceanian haplogroups in addition to many Asian and Amerindian ones. Superhaplogroup N can be divided into smaller haplogroups such as R, A, I, S, W, X and Y (Kong et al, 2011). Haplogroup N is found in all parts of the world, but has low frequencies in Sub-Saharan Africa, and can be defined by the mutations at position 8701;9540;10398;10873 and 15301 (van Oven and Kayser, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…43 The ages of the lineages G2a2 (further defined by mutation 16193 and named G2a2 tentatively) and M9a1a2a (characterized by mutations 16145, 16316 and a back mutation at site 16362, and designated as M9a1a2a) (Table 4) were estimated by using the r statistic 44,45 with the suggested calibration rates. 44,46 RESULTS AND DISCUSSION On the basis of the combined information from control-region and partial coding-region segments, the majority (96.34%; 237/246) of the Nepalese mtDNAs could unambiguously be allocated into the defined haplogroups of East Eurasian (36.59%; 90/246), 1,[20][21][22][23][24][25] Table S1, Supplementary Material online), 5 and this pattern remains almost stable for both the East Eurasian (45.11%; 189/419) and South Asian (47.49%; 199/419) components after taking into account the recently reported Nepalese mtDNA data. 5 As for the 21 samples with ambiguously phylogenetic status, completely sequencing their mtDNA genomes revealed that virtually all of these samples in fact belong to the already defined haplogroups, such as M3, M5, M18, M30, M35, M43, D4, R8 and M60.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the updated phylogenetic tree of China with the entire mtDNA genomes Zhao et al, 2009;Kong et al, 2003bKong et al, , 2006Kong et al, , 2011, the quality strategy (Bandelt et al, 2001;Parson and Bandelt, 2007), and the coding region variations typing strategy for verifying the haplogroup status (Yao et al, 2004), mtDNA has offered the fundament for tracing the prehistory origin and migration scenarios at maternal aspect. Thus, the more mtDNA datasets from the crucial geographical region, Hunan, south-central China, will offer more data for tracing the migration and expansion of the anatomically modern human to this area.…”
Section: Introductionmentioning
confidence: 99%